2012
DOI: 10.1021/jp303187z
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the LCST on the Liquid–Liquid Equilibrium of Thiophene with Ionic Liquids

Abstract: Mixtures of thiophene with two ionic liquids, namely, [C(4)C(1)im][SCN] and [C(4)C(1)im][NTf(2)], were chosen as prototypes of systems presenting lower critical solution temperature (LCST) and upper critical solution temperature (UCST) behavior, respectively. This distinct behavior is due to different interactions between the constituting species which are investigated here by means of experimental and computational studies. Experimentally, density measurements were conducted to assess the excess molar volumes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…As already apparent from the discussion so far, UCST and LCST are not exclusive features of IL/water solutions but can be observed in systems made of IL in a variety of organic molecular solvents. Interesting, in this respect, is the study in reference [ 128 ], comparing the solubility in thiophene of [bmim][SCN] and [bmim][NTf ], whose temperature dependence displays a LCST for the former, and a UCST for the latter. The analysis of interactions by the experimental determination of the molar volumes and by NMR in the mixed and demixed phases and by MD simulations highlights an attractive interaction between a thiophene proton and the S atom in [bmim][SCN], and a solvophobic character of [bmim][NTf ] in thiophene.…”
Section: Overview Of Experimental and Computational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As already apparent from the discussion so far, UCST and LCST are not exclusive features of IL/water solutions but can be observed in systems made of IL in a variety of organic molecular solvents. Interesting, in this respect, is the study in reference [ 128 ], comparing the solubility in thiophene of [bmim][SCN] and [bmim][NTf ], whose temperature dependence displays a LCST for the former, and a UCST for the latter. The analysis of interactions by the experimental determination of the molar volumes and by NMR in the mixed and demixed phases and by MD simulations highlights an attractive interaction between a thiophene proton and the S atom in [bmim][SCN], and a solvophobic character of [bmim][NTf ] in thiophene.…”
Section: Overview Of Experimental and Computational Studiesmentioning
confidence: 99%
“…Atomistic MD simulations of thermoresponsive IL/water solutions have, until now, played different roles from that of thermodynamic models, since MD cannot be used for the extensive screening of hundred of compounds, although MD has contributed significant insight into these systems and phenomena. A clear distinction between the contribution of experiments and simulations to the understanding of thermoresponsive IL solutions is not really possible, at least because several studies combine both approaches (see, for instance, references [ 32 , 76 , 128 ]). Nevertheless, it is also possible to observe that, in this field, the strength of simulation has been in providing structural details and mechanisms down to the atomistic level.…”
Section: The Role Of Computational Modelingmentioning
confidence: 99%
“…However, compared with polymeric LCST systems, only a limited number of smaller molecules-containing systems has been developed exhibiting LCST behavior and adjustable thermo-responsive properties. These include ionic liquids [2730], macrocycles [3134], and supramolecular pairs [26,3538]. For example, the combination of macrocycles and supramolecular interactions can realize controlled release and product separation in complex supramolecular systems [35].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulation is a general method in researching the LCST phase behavior on an atomic or a molecular level . For example, Batista et al studied the mixture system of thiophene and 1-butyl-3-methylimidazolium thiocyanate ([C 4 C 1 im]­[SCN]) by using MD simulation. It was found that the LCST phase behavior of mixture was caused by the interactions of [SCN] − with thiophene.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulation is a general method in researching the LCST phase behavior on an atomic or a molecular level. 17 For example, Batista et al 18 S1), the reported AMBER all-atom force field parameters were used, 20,21 and the SPC model of H 2 O was adopted. 22 By using the Gaussian 09 D.01 version, 23 the ion pair structures were optimized at the B3LYP/6-31+G* level.…”
Section: Introductionmentioning
confidence: 99%